(3GSS hGYJHGQGJ JfejI GdXgjQ GdNdai defGWb GdJfejI GdSjGMjI GdSGMdjI (B: s (3HGdJWHjb Ydi SGMd GdHMQ GdGMeQ (B/ s - (3MSGe GdOjf eMeO GfhQs; (3MSf HgLJ (B: s; (3SGeM GdYdGjdi (B: s; (3SgGe GHhSQjY (B: s ((3GdbGgQI (B: s (3MSGe GdOjf eMeO GfhQ (B: s, 2008)
(3jbhe GdHMK HJMOjO GdeTcdI GdQFjSjI hUjGZJgG ai UhQI YThGFjI JfejI XgjQ GdefGWb GdSGMdjI NGQL cQOhfGJ GdeOf cQO aYd JdbGFi dJdHjI GMJjGLGJ GdTQjW GdSGMdi HJdc GdefGWb MjK jHMK eLehYI ef GdGgOGa JJeKd ai JMOjO eaghe XgjQ efGWb GdJfejI hGdeaghe GdhXjai hGdGWGQ GdYGe dJfejJI ai GWGQ eaghe GdJfejI GdSGMdjI GdeJcGedI HGdGVGaI Gdi OQGSI eLehYI GdGSS hGdGYJHGQGJ GdJUejejI GdJi JDKQ hHTcd eHGTQ Ydi GdJTcjd GdaQGZi hGdYeQGfi ddeQcR GdSjGMis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJNWjW GdGbdjei h GdYeQGfi (B- (3bSe GdJUeje GdYeQGfis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSS hGdGYJHGQGJ GdJUejejIs; (3GdeQGcR GdSjGMjI GdeJcGedIs; (3JfejI GdXgjQ GdSjGMis